Utilization of Gliricidia sepium and cassava peels by West African Dwarf goats in Nigeria - Ifut, O.J. (1989)
Three diets - 100% Gliricidia septum (T-1), 100% cassava peels (T-2) and 70% Gliricidia septum plus 30% cassava peels (T-3) were fed to 12 intact bucks of the West African Dwarf (WAD) breed in a completely randomised experiment. Four bucks were randomly assigned to each diet treatment. The experiment lasted 90 days.Treatment effect on dry-matter intake (DMI) was significant (P<0.05). Goats on T-3 consumed the highest dry matter (DM), organic matter (OM), nitrogen (N), acid-detergent fibre (ADF) and neutral-detergent fibre (NDF), digestible DM (DDM), digestible OM (DOM), digestible ADF (DADF) and digestible NDF (DNDF) while those on T-2 consumed the least. Goats on T-1 had the highest digestible N intake (DNI).Goats on T-3 digested DM, N, ADF and NDF most (P<0.05); those on T-2 digested OM most; they also had negative N digestibility and digested ADF and NDF least (P<0.05). Goats on T-1 digested DM and OM least (P<0.05).The highest (P<0.05) body weight gain was by goats on T3 while those on T-2 were losing weight daily.Gliricidia septum was the most and cassava peels the least (P<0.05) efficiently utilized as sole diets by goats.Estimated meat yield per treatment was highest for animals on T-3.The intake, digestibility and utilization for weight gain of Gliricidia septum by goats were increased by supplementation with cassava peels.